Exploring Developing World’s Readiness to Adopt Society 5.0: Pakistan’s Case in Point - Aamina Urooj (Universitas Muhammadiyah Purwokerto, 2025)
Society 5.0, advocates for a future in which technological advancement is guided by human-centered values. In simple terms it aims to create a super-smart society by integrating cyberspace and physical space with the aim of fostering a more inclusive, sustainable, and balanced society. originally envisioned in Japan, the Japanese government has been actively promoting it to address challenges like an aging population, economic stagnation and environmental concern. Some developed nations (e.g. Germany) have begun aligning their systems with similar vision. Although Pakistan, as a developing nation, remains at an early stage of digital transformation due to its unique socio-economic and infrastructural conditions, the article will explore Pakistan’s potential to adopt the principles of Society 5.0 by examining key challenges and opportunities across governance and broader socio-economic systems. Despite growing global interest in Society 5.0, existing literature largely focuses on advanced economies, leaving limited understanding of how developing countries like Pakistan might engage with this paradigm shift. Thus, employing a qualitative exploratory approach, this article assesses Pakistan’s readiness for Society 5.0.